Comparison of Soil Organic Matter Transformation Processes in Different Alpine Ecosystems in the Qinghai‐Tibet Plateau. Issue 1 (4th January 2019) - Chen, Qiuyu; Lei, Tianzhu; Wu, Yingqin; Si, Guicai; Xi, Chuanwu; Zhang, Gengxin
Abstract: Soils in the Qinghai‐Tibet Plateau are young in terms of development and form a thin, skeletal soil layer because the gravel parent materials are glaciofluvial deposit, eluvium, and fluvial sediment, which are extremely sensitive to global climate change. The lack of understanding of soil organic matter (SOM) transformation processes in this region hinders the prediction of SOM stocks under future climate conditions. In this study, SOM transformation processes were investigated by density groupings and pyrolysis‐gas chromatography/tandem‐mass spectrometry (Py‐GC–MS/MS) in five alpine ecosystems: alpine desert, alpine grassland, alpine meadow, alpine wetland, and alpine forest. The roles of microbial community in different density fractions were elucidated. Soil samples were separated into three fractions with NaI solution: labile fraction (F L ; ρ ≤ 1.6 g/cm 3 ), moderate fraction (F M ; 1.6 < ρ < 2.25 g/cm 3 ), and recalcitrant fraction (F R ; ρ ≥ 2.25 g/cm 3 ). The following results were obtained. (1) The ratios of different fractions (F M /F L, F R /F M, and F R /F L ) indicated the transformation processes of SOM, and ratios less than 1 represented degradation. The transformation processes were similar in alpine grassland and meadow and were similar in alpine desert, wetland, and forest but differed from each other. (2) Fungi preferred to degrade plant detritus, which mainly affected F L, whereas bacteria chiefly affected F M . (3) Precipitation altered vegetation type and soil pH, thus affecting communities and microorganism activities and resulting in the above differences. These findings highlight the importance of understanding the limited transformation processes of SOM in ecosystems to predict the impact of climate change on SOM preservation. Key Points: Transformation processes were similar in alpine grassland and meadow and were similar in alpine desert, wetland, and forest, but the two types of transformation processes differed Bacterial communities mainly degraded the moderate fraction (intermediate‐density fraction), whereas the fungal communities chiefly decomposed the labile fraction The main environmental factors responsible for the differences in SOM transformation among the five ecosystems were precipitation and soil pH